The Influence Of Raw Material Supply On Production Results At Adinda Embroidery Convection Tasikmalaya District - Kamal, Rapli Mustopa; Lestari, Suci Putri; Arif (Universitas Dehasen Bengkulu, 2024)
The research carried out by the author aims to find out and analyze the description of the supply of raw materials and production results at the Adinda Embroidery Convection, Tasikmalaya Regency. The influence of raw material supplies on production results at the Adinda Embroidery Convection, Tasikmalaya Regency. This research is quantitative research using the causality method with a survey approach. The sampling technique used was full sampling, namely using 48 months of data for 4 years from 2020 - 2023 at the Adinda Embroidery Convection. The analytical tool used in this research was simple regression using SPSS 26.0. The research results show that the supply of raw materials and production results at the Adinda Embroidery Convection in Tasikmalaya Regency fluctuates every month according to market conditions and consumer demand. The supply of raw materials has a significant effect on production results at the Adinda Embroidery Convection, Tasikmalaya Regency.